IMPLEMENTATION OF SERVICE DOMINANT LOGIC IN PUBLIC TRANSPORT (Case Study: Lampung Province) - , ALIF ADITYA S; , Prof. Dr. Ir. Siti Malkhamah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
sustai Private vehicle using is leading to increased traffic congestion, air pollution and mounting social disparities, especially at big city. Particularly in Lampung Province, Bandar Lampung as a capital of Lampung province is trying to initiate creating nable integrated public transportation and it has been started while several public transport companies together established Trans Bandar Lampung. At early, it was going really well and Bandar Lampung citizen started to use this Buss Rapid Transit System. However, due to Trans Bandar Lampung was built as private company, government did not fund subsidy for it. Trans Bandar Lampung started to face problem especially in maintenance term. Research methodology of this research is using qualitative research. By fitting between theories and data collection, qualitative research tends to be associated with words or images as the unit of analysis. The hypothesis was tested by spreading questioners to the respondents as primary data. The primary data is used to understand about public transport user in Lampung Province. On the other side, secondary data is used to analyze the current condition public transportation in Lampung Province. The objective of this research is to examine current condition public transport system in Lampung Province. Generating sustainable public transport system on Lampung Province, providing advice to prenting Trans Bandar lampung from collapse. Furthermore, this research also assess about performance of public transportation on Lampung. At the end, it will provide some reflection to developed counties